Comparing different methods of sampling to estimate the mineral resource in the Elizabeth Bay aeolian diamond placer - J. U. Burger (The Southern African Institute of Mining and Metallurgy, 2009)
The Elizabeth Bay aeolian deposit in Namibia comprises a sedimentary package of diamondiferous grits that have been deposited, reworked and concentrated to various degrees by dominant southerly winds. Diamond concentration in these deposits is highly variable and often unpredictable. The deposit is marginal from an economic perspective and therefore requires selective mining which in turn requires correct sampling and accurate estimation. Three methods of sampling have been used at Elizabeth Bay for mineral resource estimation: (i) pit samples utilizing an excavator to produce a sample 1 to 3 metres deep with a 10 to 20 m2 footprint, (ii)GB50 grab sampling with a 3.34 m2 footprint and (iii) a BG36 bucket auger drill with a 5 m2 footprint. Pit sampling, being easy to execute, has been the most widely used despite a limited penetration ability and, at times, questionable integrity. The GB50 grab sampling tool was tested at Elizabeth Bay and although it had better penetration ability and sample integrity, it struggled with cemented horizons. No sample optimization was conducted prior to the GB50 grab sampling. The latest phase of sampling was conducted using a BG36 bucket auger drill which is capable of penetrating thick overburden, penetrate cemented horizons and provides an acceptable sample support size. Geostatistical simulation methods were applied to establish the optimum sampling parameters required to estimate a mineral resource at an indicated level of confidence. The results show that a 5 m2 sample support size is adequate and that a 50 m 100 m sample configuration is optimal. Sample data obtained from the three methods confirms that the BG36 bucket auger tool combined with the parameters identified in this exercise produce the best results for diamond resource estimation.